2021
DOI: 10.1111/hdi.12977
|View full text |Cite
|
Sign up to set email alerts
|

Trajectories of clinical and laboratory characteristics associated with COVID‐19 in hemodialysis patients by survival

Abstract: Introduction: The clinical impact of COVID-19 has not been established in the dialysis population. We evaluated the trajectories of clinical and laboratory parameters in hemodialysis (HD) patients. Methods: We used data from adult HD patients treated at an integrated kidney disease company who received a reverse transcription polymerase chain reaction (RT-PCR) test to investigate suspicion of a severe acute respiratory syndrome coronavirus-2 (SARS-CoV-2) infection between May 1 and September 1, 2020. Nonparame… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
6
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 17 publications
2
6
0
Order By: Relevance
“…In contrast, we found that the CRP values increased from baseline data in the acute phase of infection and decreased after the infection. Likewise, other authors have found similar results in albumin and CRP (Chaudhuri et al, 2022). These biochemical modifications could also help to understand the physiological changes caused by SARS-CoV-2 in HD patients.…”
Section: Discussionsupporting
confidence: 77%
“…In contrast, we found that the CRP values increased from baseline data in the acute phase of infection and decreased after the infection. Likewise, other authors have found similar results in albumin and CRP (Chaudhuri et al, 2022). These biochemical modifications could also help to understand the physiological changes caused by SARS-CoV-2 in HD patients.…”
Section: Discussionsupporting
confidence: 77%
“…Mortality among those with COVID-19 on haemodialysis has been widely reported on, with age, frailty and co-morbidity burden featuring as strong predictors. 14 16 17 However, mortality is commonly reported as a death occurring within 28 or 30 days of a positive PCR test 77–81 and could therefore include mortalities not strictly attributable to COVID-19, particularly given the characteristics of those most at risk. Furthermore, risk factors for mortality may not be COVID-19 specific; this can be challenging to differentiate between and therefore act on from a public health perspective.…”
Section: Discussionmentioning
confidence: 99%
“…Most studies that have investigated COVID-19 among those receiving haemodialysis examined risk of mortality, mostly reporting age, frailty and comorbidity burden as important predictors. 14–19 Severe disease represents a different but important clinical outcome, conferring significant mental and physical morbidity, and may have different risk factors that associate with it. 2 20–23 Associations with this outcome have not been investigated in detail among patients receiving haemodialysis.…”
Section: Introductionmentioning
confidence: 99%
“…As the COVID-19 pandemic evolves, it is unclear whether or not previously identified predictors [e.g., residing in a nursing home in (14, 15), clinical and laboratory parameters in (15)(16)(17)] are still predictive and previously built machine learning models [e.g., XGBoost in (13)] are still effective for the early detection of COVID-19 cases. Not only has the original virus undergone mutations that have resulted in multiple variants with different clinical presentations (18-20), but also the social environment has significantly changed.…”
Section: Introductionmentioning
confidence: 99%